Die deutsche Fischerei auf den "ozeanischen" Rotbarsch (Sebastes mentella) von 1995 bis 1998 - Rätz, Hans-Joachim; Stransky, Christoph (1999)
Recently, the German redfish fishery displayed a pronouncedseasonal pattern in geographic effort distribution and depth. The second and third quarters were the main season when 80 % of the effort was exerted. During the second quarter, the fleet activities were concentrated in international waters close to the Icelandic Exclusive Economic Zone (EEZ), fishing at depths exceeding 600 m. In contrast, the catches in the third quarter were taken mainly inside the Greenland EEZ at depths around 300 m. From 1995 to 1998, the annual effort ranged from 14 000 to 18 000 trawling hours, without a trend. This effort yielded about 18 000 to 21 000 t (international catch > 100 000 t) annually. Since 1996, the catch rate (CPUE) decreased during the main season. The decrease in CPUE should be interpreted as the first reaction of the stock to increased exploitation. The fish size also varied seasonally and peaked during the second quarter at depths exceeding 600 m. Here, males were bigger than females and both sexes were equally frequent. The increase of fish size with increasing depth did not contribute to the hypothesis of two separate pelagic redfish stocks above and below 500 m. In contrast, the close relation between fish size and depth point to the so-called “deeper-bigger phenomenon” which was found in numerous fish stocks. Very few redfish in the catches were immature. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.